The potential of coal mine voids for clean water sources in Nusantara Capital City - Hasan, Harjuni; Sarwono, Edhi (Journal of Degraded and Mining Lands Management, 2024)
PT. Singlurus Pratama operates four mining blocks: Sungai Merdeka, Argosari, Margomulyo, and Mutiara. he Sungai Merdeka block has three voids with significant potential as a source of clean water for Nusantara Capital City (IKN), given its location within the city's development area. Surface water flows from the southern ridge to the north, accumulating in the voids of the Sungai Merdeka block, with a total inflow of 449,218,750 m³ per day. This volume can meet the needs of 1,796,875 to 4,492,187 people. One of the geological formations of the Sungai Merdeka block is the Balikpapan Formation, composed of alternating sandstone and clay with intercalations of shale and limestone, which is likely an aquifer. The water quality in voids 1 and 2 falls into the fairly good category (WQI = 70.07 and 70.77), while void 3 has moderate quality (WQI = 64.76). Thus, the water from the Sungai Merdeka voids can be used for personal and household hygiene, as well as raw water for drinking. Additionally, it can be utilized for recreational water facilities, freshwater aquaculture, livestock, and irrigation. However, the void water in the Sungai Merdeka block is indicated to have formed acid mine drainage, as the exposed void walls are contaminated with oxygen and leached by water. This leads to increased acidity, as indicated by the low pH values of the water. The increased acidity also results in higher concentrations of dissolved metals within the voids, necessitating careful management and treatment to ensure the water’s safety and usability for various applications.